(untitled) (Itinera, 2024)
Gilbert Simondon was among the first to observe the rise of planetary technologies and to integrate this phenomenon into his philosophy. Already since On the Mode of Existence of Technical Objects, Simondon claimed that technology is endowed with an intrinsic ecumenic tendency and that this tendency is manifesting through the technical ensembles of the informational era: technics is constructing the Earth as a new «techno-geographic environment». This paper aims at analyzing Simondon’s view on planetary technology and infrastructural networks, also in the light of the structural instability characterizing today’s social and natural systems. In the conclusions, an alternative way towards cultural progress is suggested, the one that Simondon discarded: the way of “aesthetics after aesthetics”. Aesthetics might in fact offer a different model to situate the human groups in the techno-planetary environment and overcome extractivist authoritarianism, as long as it finds effective realization into a neo-magic paradigm.